2010
DOI: 10.1261/rna.2091710
|View full text |Cite
|
Sign up to set email alerts
|

A novel mRNA affinity purification technique for the identification of interacting proteins and transcripts in ribonucleoprotein complexes

Abstract: Intracellular mRNA targeting and localized translation are potential determinants for protein localization. To facilitate targeting, mRNAs possess specific cis-acting sequence motifs that are recognized by trans-acting RNA-binding proteins (RBPs). While many mRNAs are trafficked, our knowledge of the RBPs involved and presence of additional transcripts within these ribonucleoprotein (RNP) complexes is limited. To facilitate the identification of RBPs and transcripts that bind to specific mRNAs, we developed RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 48 publications
1
73
0
Order By: Relevance
“…This study was important not only to help validate previous cell fractionation/transcriptome analyses, but also as a stepping stone to using mRNA affinity purification techniques to identify RBPs and other elements involved in mMP localization (Slobodin and Gerst 2010). Out of the 24 endogenously expressed mMPs examined (z4% of nuclear-encoded mitochondrial genes), at least 17 appeared to show colocalization with mitochondria ( Fig.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This study was important not only to help validate previous cell fractionation/transcriptome analyses, but also as a stepping stone to using mRNA affinity purification techniques to identify RBPs and other elements involved in mMP localization (Slobodin and Gerst 2010). Out of the 24 endogenously expressed mMPs examined (z4% of nuclear-encoded mitochondrial genes), at least 17 appeared to show colocalization with mitochondria ( Fig.…”
Section: Discussionmentioning
confidence: 87%
“…While it is unclear how mMPs target to (or associate with) the ER, mRNAs like OXA1 may use nonessential components of the ERMES complex (e.g., Mdm10) for ER attachment (Tables 1, 2). Recent work from our laboratory demonstrated that factors involved in protein trafficking to the ER (e.g., Sec27/b9COP) bind to OXA1 mRNA and facilitate its association with mitochondria (Slobodin and Gerst 2010). Thus, some mMPs may be targeted to ERMES/SAM-marked intermembrane contact sites, perhaps to facilitate protein import into the mitochondria at these foci.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we do not know whether translation-activating signals act on the individual mRNA species or on ribonucleoprotein (RNP) complexes in which transcripts coding for proteins with complementary function are co-packaged. Association of RNA-binding proteins with discrete sets of mRNAs coding for functionally related proteins and co-existence of several mRNA species within shared RNP complexes has been unambiguously demonstrated in yeast [94,95], and is proposed to exist in eukaryotic cells [96][97][98]. If these putative post-transcriptional RNA operons exist in axons it will be an interesting idea to target the formation or the axonal transport of the multifunctional RNP in order to interfere with intra-axonal protein synthesis of a cohort of functionally related proteins.…”
Section: Perspective/challengesmentioning
confidence: 99%
“…Regarding the latter, most widely used are the coat proteins from the R17/MS2 bacteriophage and streptavidin S1, a bacterial protein, both of them interacting with short hairpin RNA structures [20][21][22][23][24]. The repeats of the MS2 or S1 binding RNA stem loop are appended to a RNA of interest and the tagged RNA complex is then purified by coupling of the respective protein to a solid support or resin [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the latter, most widely used are the coat proteins from the R17/MS2 bacteriophage and streptavidin S1, a bacterial protein, both of them interacting with short hairpin RNA structures [20][21][22][23][24]. The repeats of the MS2 or S1 binding RNA stem loop are appended to a RNA of interest and the tagged RNA complex is then purified by coupling of the respective protein to a solid support or resin [20][21][22][23][24]. While these indirect RBPmediated approaches are relatively versatile and represent an efficient tool for RNA localization studies [25][26][27], a major drawback is the indirect nature of the interaction, making it prone to artefacts resulting from the ectopic expression of the protein, cross-reactivity with untagged RNAs, interference with native RNP formation, and unspecific interactions.…”
Section: Introductionmentioning
confidence: 99%